Thermal pre-treatment – A prerequisite for the reduction of hydrolysis stage during anaerobic digestion of Ageratum conyzoides - Biswanath Saha (KeAi Communications Co., Ltd., 2021)
The present study mainly focussed on the effect of different thermal pretreatments on Ageratum conyzoides. Thermal pretreatment reduced the hydrolysis period and, at the same time, increased biogas production as compared to the untreated Ageratum conyzoides. The effects of four different thermal pretreatment techniques, i.e., hot air oven, microwave, autoclave, and hot water bath on the anaerobic digestion of Ageratum conyzoides were studied. Autoclave pretreatment was found to be more efficient, followed by a hot water bath, hot air oven, and microwave pretreatments. Autoclave pretreatment enhanced the solubilization. Simultaneously, increment in volatile fatty acids and soluble chemical oxygen demand was observed as 55.33% and 54.59% for autoclave at 90° C for 90 min, respectively, compared to the control/untreated. After autoclave pretreatment, cumulative methane production rose to 4053 mL CH4/g VS in 35 days from 3011 mL CH4/g VS in 50 days for the untreated sample.